2023
DOI: 10.7759/cureus.44402
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Fetal Outcomes and Histopathology of Placentas Affected by COVID-19: A Report of Four Cases

Megan Corn,
Truc Pham,
Walter Kemp

Abstract: Coronavirus disease 2019 (COVID-19) has had significant impacts on mothers and neonates. In this report, we present four unique cases of COVID-19 infections in pregnancy and its effects on the mother, fetus, and placenta. Four mothers presented to the hospital during their pregnancy. Each had tested COVID-19-positive 1-29 days prior to admission. Gestational age ranged from 16 weeks six days to 36 weeks six days. Three of the four cases resulted in fetal demise or infant expiration. The common finding among al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…We identified CD68 + macrophages in the chorionic plate, chorionic villi, and decidua basalis. Other reports have identified macrophages in the intervillous space of the chorionic villi in SARS-CoV-2-associated fetal demises, consistent with one criterion of the SARS-CoV-2 placentitis triad [ 6 , 14 , 17 , 18 ]. We additionally reported the presence of other immune cells, such as neutrophils, plasma cells, CD56 + NK cells and a few CD8 + T lymphocytes, which are implicated in antiviral responses, at sites of placental inflammation.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…We identified CD68 + macrophages in the chorionic plate, chorionic villi, and decidua basalis. Other reports have identified macrophages in the intervillous space of the chorionic villi in SARS-CoV-2-associated fetal demises, consistent with one criterion of the SARS-CoV-2 placentitis triad [ 6 , 14 , 17 , 18 ]. We additionally reported the presence of other immune cells, such as neutrophils, plasma cells, CD56 + NK cells and a few CD8 + T lymphocytes, which are implicated in antiviral responses, at sites of placental inflammation.…”
Section: Discussionsupporting
confidence: 69%
“…We additionally reported the presence of other immune cells, such as neutrophils, plasma cells, CD56 + NK cells and a few CD8 + T lymphocytes, which are implicated in antiviral responses, at sites of placental inflammation. Most cases reported the localization of SARS-CoV-2 spike and nucleocapsid antigens in syncytiotrophoblasts [ 9 , 19 ], cytotrophoblasts [ 19 ], within villous stromal cells including Hofbauer cells and villous capillary endothelial cells [ 20 , 21 ], and on the maternal side of the placenta [ 18 , 21 ]. We detected the SARS-CoV-2 nucleocapsid in both maternal decidual cells and fetal stromal cells of the chorion and chorionic villi, consistent with the sites of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent reports confirmed that the histopathological triad of SP was robust and reliable, facilitating the recognition of new cases of SARS-CoV-2 infection in the placenta. The term SP has become universally accepted [24,[36][37][38][39][40][41].…”
Section: Sars-cov-2 Placentitismentioning
confidence: 99%
“…The inflammatory infiltrate in SP is patchy and rather scarce and, besides histiocytes, contains various numbers of neutrophils and lymphocytes [16,24,35]. In addition, unlike in CHI, PVFD in SP is marked and frequently massive, occupying more than 25% of the placental disc (and greater than 75% in cases of intrauterine fetal demise [38,41]). Finally, SP is characterized by extremely pronounced trophoblast necrosis due to combined effects of the complement-mediated immunological damage of this cellular layer, direct viral cytopathic change, and associated apoptosis [16,24,35,42].…”
Section: Sars-cov-2 Placentitismentioning
confidence: 99%
See 1 more Smart Citation